Experimental Study on How 10 weeks of Combined Height Interval Intensity Training (HIIT) and Plyometric Training Can Affect Explosive Power in U17 Football Players - Abderrahim Laidi; Hassan Melki; Makhlouf Djerioui; Layachi Salem (Слобожанський науково-спортивний вісник)
Background and Study Aim: Examining how a ten-week training program combining high-intensity interval training (HIIT) and plyometric exercise can affect explosive strength levels among under 17-year-old football players.